(Table 1) Basement lithologic units at DSDP Leg 65 Holes - Ron Day (PANGAEA, 1983)
The principal objective of DSDP Leg 65 was to sample oceanic crust near the crest of the East Pacific Rise. The sites that we drilled, close to the mouth of the Gulf of California, are areas where the sedimentation rate is high and where high seismic velocities indicated that the basement could be successfully drilled. We occupied four sites (482-485) and drilled 15 holes, of which 8 reached basement. Although we attempted to drill re-entry holes at Sites 482 and 483, we lost them because of operational problems.
Supplement to: Day, R (1983): Paleomagnetism of igneous rocks from Deep Sea Drilling Project Sites 482, 483, and 485. In: Lewis, BTR; Robinson, P; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 65, 705-715, https://doi.org/10.2973/dsdp.proc.65.138.1983